1996
DOI: 10.2337/diacare.19.5.423
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Socioeconomic Status and Diabetes Control and Complications in the EURODIAB IDDM Complications Study

Abstract: Healthy lifestyles are more prevalent in better educated men and women with IDDM, but these are not reflected in heart disease prevalence in men. The lower prevalence of severe microvascular complications in better educated men, unaccounted for by better glycemic control, requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
94
3
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 20 publications
14
94
3
1
Order By: Relevance
“…22 In our study, diabetic people with higher education had a lower prevalence of current smoking and a higher proportion of regular exercise as compared with those with lower education. However, adjustment for smoking and regular exercise in our own analysis did not change the results substantially.…”
Section: Discussionmentioning
confidence: 65%
“…22 In our study, diabetic people with higher education had a lower prevalence of current smoking and a higher proportion of regular exercise as compared with those with lower education. However, adjustment for smoking and regular exercise in our own analysis did not change the results substantially.…”
Section: Discussionmentioning
confidence: 65%
“…Although the best chances of preventing visual loss are when DR is treated before symptoms occur, about 1 in 5 patients are referred late to specialists [38]. Poor education and lower socio-economic status are strongly associated with PDR and visual loss, both in the United States [39] and Europe [40].…”
Section: Diabetes-related Blindnessmentioning
confidence: 99%
“…As mentioned above, poor schooling and lower socio-economic status are associated with diabetesrelated visual loss [39,40] and more should be done to encourage patients' active participation in optimizing their blood glucose and pressure and having regular eye checks. Educational methodologies should start with structured studies of patients and their beliefs and attitudes.…”
Section: Screening In the Patients' Perspectivementioning
confidence: 99%
“…14 have looked at overall retinopathy, rather than considering different stages of the disease, and studies by Chaturvedi et al 15 and Hanna et al 16 have found significant socioeconomic variations in the prevalence of proliferative diabetic retinopathy. In the classification system used in Gloucestershire, proliferative retinopathy is graded as sight threatening, though this classification also includes maculopathy, moderate to severe non-proliferative retinopathy and advanced retinopathy.…”
Section: Discussionmentioning
confidence: 99%